An intensive assessment of alcohol use and emergency department utilization in homeless alcohol-dependent adults. (1st September 2017) - Holtyn, August F.; Jarvis, Brantley P.; Subramaniam, Shrinidhi; Wong, Conrad J.; Fingerhood, Michael; Bigelow, George E.; Silverman, Kenneth
Highlights: Alcohol intoxication was the most common reason for emergency department use. Homeless adults with emergency department use had more alcohol-positive breath samples. Homeless adults with emergency department use had higher rates of heavy alcohol use. Abstract: Background: Excessive alcohol use among the homeless may contribute to their high rates of emergency department use. Survey-based studies have provided some information on the relation between alcohol and emergency department use among the homeless. Methods: This study used an intensive schedule of random breath collections and self-report assessments to examine the relation between emergency department utilization and alcohol use in homeless alcohol-dependent adults. Data were from homeless alcohol-dependent adults (N = 116) who were participating in a therapeutic workplace that provided job-skills training every weekday for 26 weeks. Breath-sample collections and assessments of self-reported alcohol use were scheduled each week, an average of twice per week per participant, at random times between 9:00 A.M. and 5:00 P.M. Participants received 35 for each breath sample collected. Self-reports of emergency department use were assessed throughout the study. Results: Thirty-four percent of participants reported attending an emergency department and reported an average of 2.2 emergency department visits (range 1–10 visits). Alcohol intoxication was the most common reason for emergency department use. Participants who used the emergency department had significantly more alcohol-positive breath samples and more self-reported heavy alcohol use than participants who did not use the emergency department. Conclusions: This study provided a rare intensive assessment of alcohol and emergency department use in homeless alcohol-dependent adults over an extended period. Emergency department use was high and was significantly related to indices of alcohol use.